2020
DOI: 10.3390/brainsci10100684
|View full text |Cite
|
Sign up to set email alerts
|

Painful Cutaneous Electrical Stimulation vs. Heat Pain as Test Stimuli in Conditioned Pain Modulation

Abstract: Different paradigms can assess the effect of conditioned pain modulation (CPM). The aim of the present study was to compare heat pain, as an often used test stimulus (TS), to painful cutaneous electrical stimulation (PCES), having the advantage of the additional recording of PCES-related evoked potentials. In 28 healthy subjects we applied heat and PCES at the dominant hand as test stimulus (TS) to compare the CPM-effect elicited by hand immersion into cold water (10 °C) as conditioning stimulus (CS). Subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The aim of the study was to investigate the pain modulatory function in patients with PTH as a possible contributing mechanism, based on a novel recently established testing paradigm CPM 35 , 41 , 42 including electrophysiological parameters after electrical stimulation as an objective readout. Additionally, we recorded PREP as previous studies on primary headaches and trigeminal neuralgia indicated that increased PREP amplitudes might be useful as a marker for central sensitisation 16 , 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the study was to investigate the pain modulatory function in patients with PTH as a possible contributing mechanism, based on a novel recently established testing paradigm CPM 35 , 41 , 42 including electrophysiological parameters after electrical stimulation as an objective readout. Additionally, we recorded PREP as previous studies on primary headaches and trigeminal neuralgia indicated that increased PREP amplitudes might be useful as a marker for central sensitisation 16 , 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as mentioned previously, different modalities (thermal, mechanical, electrical, etc.) used as TS and/or CS appear to vary in their ability to evoke CPM or TSP ( 30 , 36 38 ). While these studies differ somewhat in the specifics of their findings, a general emerging trend suggests that electrical stimulation (either as the TS, the CS, or both) tends to be less suited than other types of stimulation to evoke CPM.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known however about potential differences in the magnitude of the CPM effect between a sequential or parallel design. Indirect studies reported conflicting results, showing no differences between both designs ( Ibancos-Losada et al, 2020 ), larger effects for either a parallel ( Nahman-Averbuch et al, 2013 ; Ram et al, 2008 ) or sequential ( Enax-Krumova et al, 2020 ) design. Moreover, statistical comparisons between the two designs were often not performed ( Enax-Krumova et al, 2020 ; Nahman-Averbuch et al, 2013 ; Ram et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%